The Sustainable Conservation of the E-Pok Puppet: An Intangible Cultural Heritage of Luang Prabang - HAEKHAM, Sonesay; KEOBOALAPHET, Soulideth; Duangchan, Boy (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This research explores the sustainable conservation of the E-Pok puppet theatre, an important form of intangible cultural heritage in Luang Prabang. Using qualitative methods, the study includes interviews with key stakeholder groups: elder performers skilled in the traditional art, younger performers as potential successors, community members from Xieng Thong and Kiri villages, officials from the Department of Information, Culture and Tourism of Luang Prabang Province, and 15 cultural heritage experts. Data was collected through surveys and both structured and unstructured interviews. The findings reveal that the E-Pok puppet theatre possesses significant historical, cultural, and spiritual value, reflecting the traditions and beliefs of the local community. However, its preservation is challenged by declining interest among younger generations, the need to adapt performances for contemporary audiences, and inconsistent funding. To address these challenges, the study proposes three key strategies for sustainable conservation: (1) encouraging youth engagement and participation, (2) integrating the performances into the tourism sector to generate income and raise awareness, and (3) digitally recording the performances and implementing a comprehensive promotional communication plan.